2003
DOI: 10.1007/s00428-003-0887-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered aquaporin 4 expression in muscles of Fukuyama-type congenital muscular dystrophy

Abstract: This study was undertaken to investigate the expression of aquaporin 4 (AQP4) in the muscle plasma membrane of children with Fukuyama-type congenital muscular dystrophy (FCMD) at protein and mRNA levels. The biopsied six muscles with FCMD, six histochemically normal muscles and eight disease control muscles were analyzed by means of immunoblots, immunohistochemistry and reverse-transcription polymerase chain reaction (RT-PCR). Immunoblots showed that the band of FCMD muscle extracts stained with anti-AQP4 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…AQP4 is expressed in healthy brain and muscle tissues (39) and well known to associate with neuromyelitis optica. The AQP4 expression is also reduced in the skeletal muscle in patients with Duchenne muscular dystrophy, Fukuyama-type congenital muscular dystrophy, and sarcoglycanopathy (39)(40)(41). In the present study, the IHC analysis revealed a decrease in the AQP4 expression in both regenerating fibers and many non-necrotic fibers in patients with IMs, particularly PM.…”
Section: Discussionsupporting
confidence: 60%
“…AQP4 is expressed in healthy brain and muscle tissues (39) and well known to associate with neuromyelitis optica. The AQP4 expression is also reduced in the skeletal muscle in patients with Duchenne muscular dystrophy, Fukuyama-type congenital muscular dystrophy, and sarcoglycanopathy (39)(40)(41). In the present study, the IHC analysis revealed a decrease in the AQP4 expression in both regenerating fibers and many non-necrotic fibers in patients with IMs, particularly PM.…”
Section: Discussionsupporting
confidence: 60%
“…Why AQP4 is important for the therapy of muscular dystrophies is based on the following facts. Firstly, both dystrophin negative muscles with Duchenne muscular dystrophy and dystrophin positive muscles with Fukuyama muscular dystrophy contain the markedly decreased AQP4 molecule (Wakayama et al, 2002a(Wakayama et al, , 2003. Secondly, the muscles of mdx mice showed the decreased expression of AQP4 (Shibuya and Wakayama, 1988;Liu et al, 1999), although the AQP4 depletion was more marked in the muscles of Duchenne and Fukuyama muscular dystrophies.…”
Section: Discussionmentioning
confidence: 97%
“…This might be considered that other AQPs such as AQP3 and 7 compensated the water-transporting function across the muscle plasma membrane instead of AQP4 in the AQP4 knockout mice, although the expression of AQP3 and 7 in skeletal muscle is not a general view (Yang et al, 2000;Frigeri et al, 2004). Recently the marked decrease of AQP4 expression in the surface membranes of skeletal myofibers in human muscular dystrophies and their animal models including mdx mice, the mouse model of Duchenne muscular dystrophy, has repeatedly described (Frigeri et al, 1998;Liu et al, 1999;Frigeri et al, 2001;Crosbie et al, 2002;Wakayama et al, 2002aWakayama et al, , 2003. In addition, the OA, which is the ultrastructure of AQP4 molecule (Frigeri et al, 1995;Yang et al, 1996;Verbavatz et al, 1997;Rash et al, 1998;Shibuya et al, 1999), is more numerous in younger mouse than the older one (Shibuya and Wakayama, 1991).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be achieved through an integrated approach involving gene expression studies (geneST arrays) and protein antibody arrays. GeneST arrays are expected to give global muscle expression profile and indicate the variability in gene expression by identifying the up and down regulated genes (Vachon, Loechel et al 1996;Tsao and Mendell 1999;Yamamoto, Kato et al 2004;Wakayama, Inoue et al 2008). Also active patient registries should be maintained for each disease type to provide ready access to a pool of information including clinical presentations and causative mutations.…”
Section: Summary and Future Directionsmentioning
confidence: 99%